Comparative study of (0.5%) levobupivacaine and (0.75%) ropivacaine in supraclavicular brachial plexus block by lateral approach - Kumar, Jitesh; Sweta, .; Lata, Kumari Kanak; Prasad, B. K.; Gupta, V. K. (International Journal of Research in Medical Sciences, 2017)
Background: As compared to general anaesthesia, brachial plexus block for upper limb surgery gives fewer side effects and better postoperative analgesia. The objective of this study was to evaluate the effects of 0.5% levobupivacaine and compare it with 0.75% ropivacaine. Methods: For this prospective randomized, controlled study, 60 patients of both sexes of ASA grade 1 and 2 were enrolled and divided into two groups and supraclavicular brachial plexus block was performed by lateral approach using 30 ml of 0.5% levobupivacaine and 0.75% ropivacaine. The onset of sensory and motor block, duration of sensory and motor block and analgesia and possible adverse events were recorded. Results: No statistically significant difference was observed in the onset of sensory block in both groups. Onset of motor block was significantly faster in levobupivacaine group (P<0.05). Duration of sensory block, motor block and analgesia was significantly longer in levobupivacaine group (P<0.05). Conclusions: 0.5% levobupivacaine is better alternative to 0.75% ropivacaine in brachial plexus block in term of early onset of sensory block and long duration of analgesia.